2021
DOI: 10.1093/rheumatology/keab748
|View full text |Cite
|
Sign up to set email alerts
|

In systemic sclerosis, the TAPSE/sPAP ratio can be used in addition to the DETECT algorithm for pulmonary arterial hypertension diagnosis

Abstract: Objective Early detection of pulmonary arterial hypertension (PAH) is crucial to improve patient outcomes. The aim of this study was to compare the positive predictive value (PPV) between the echocardiography-derived tricuspid annular plane systolic excursion/systolic pulmonary artery pressure (TAPSE/sPAP) ratio and the DETECT algorithm for PAH screening in a cohort of systemic sclerosis (SSc) patients. Methods 51 SSc patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Exercise tests may unmask impaired RV function when the right ventricle at rest still looks normal and functions well. TAPSE/sPAP ratio has already been shown to be crucial for the identification of patients at risk for PH and has been used as tool to identify SSc patients in need of more extensive diagnostics by RHC [41]. The identification of RV output reserve as an independent risk factor in this study confirms the crucial role of exercise testing in patients with SSc to identify early stages of pulmonary hypertension which has been highlighted before [4,13,[54][55][56].…”
Section: Prognostic Meaning Of Rv Function and Reserve In Different E...supporting
confidence: 73%
See 1 more Smart Citation
“…Exercise tests may unmask impaired RV function when the right ventricle at rest still looks normal and functions well. TAPSE/sPAP ratio has already been shown to be crucial for the identification of patients at risk for PH and has been used as tool to identify SSc patients in need of more extensive diagnostics by RHC [41]. The identification of RV output reserve as an independent risk factor in this study confirms the crucial role of exercise testing in patients with SSc to identify early stages of pulmonary hypertension which has been highlighted before [4,13,[54][55][56].…”
Section: Prognostic Meaning Of Rv Function and Reserve In Different E...supporting
confidence: 73%
“…Known thresholds for the above-listed parameters include TAPSE <18 mm, having already shown prognostic significance [39,40], TAPSE/sPAP ratio ≤0.6 mm/ mmHg [41] and RV pulmonary vascular reserve of ≥3 ml/min/mmHg [42], which has been used as the definition of exercise pulmonary hypertension [43].…”
Section: Parameters Of Right Ventricular Function and Reservementioning
confidence: 99%
“…TAPSE/sPAP ratio is a powerful predictor of all-cause mortality in patients with PAH. In SSc patients, TAPSE/ sPAP ratio can be used to further select patients requiring right heart catheterization to confirm PAH diagnosis and it showed the best correlation with ventilatory efficiency and exercise capacity [27,28]. There are no data in the literature showing the role of sST2 in right ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, sPAP is the most used echocardiograpic parameter to evaluate PAH. In our previous study, we demonstrated that in SSc patients with a DETECT algorithm step 2 total score > 35 TAPSE/sPAP ratio can be used to further select patients requiring RHC to confirm PAH diagnosis [14]. Dumitrescu et al investigated the role of CPET in early PAH detection in a prospective study of 173 SSc patients, without known PAH, who also underwent RHC.…”
Section: Discussionmentioning
confidence: 99%